Pavement Binder Course Optimization - Alazawi, Abrar; Al-Mousawi, Hassan Musa (Al-Nahrain Journal for Engineering Sciences, 2023)
The main objective of this study is to design the asphalt pavement structure for the Alkut-Mayssan highway in Iraq as a case study by using PCASE application to determine the necessary thickness of CR-modified asphaltic layers. Additionally, Marshall tests were used to investigate the effect of the dry process crumb rubber modifier on the thickness of the binder coarse layer based on various variables, such as the crumb rubber modifier with different content (1, 2, 3, 4, 5)% and sizes (0.3mm, 2.36mm , 4.75mm, and mix gradation). The test results show that while pavement thickness reduced as crumb rubber gradation increases, MR values increase. Additionally, as compared to the control mixture, the addition of 1% of CR in various gradations could decrease the thickness of the asphalt binder layer.